2015
DOI: 10.1111/1462-2920.12849
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Pseudomonas aeruginosa type IV pili and regulation of their function

Abstract: SummaryType IV pili (T4P) are bacterial virulence factors involved in a wide variety of functions including deoxyribonucleic acid uptake, surface attachment, biofilm formation and twitching motility. While T4P are common surface appendages, the systems that assemble them and the regulation of their function differ between species. Pseudomonas aeruginosa, Neisseria spp. and Myxococcus xanthus are common model systems used to study T4P biology. This review focuses on recent advances in P. aeruginosa T4P structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 144 publications
(256 reference statements)
1
78
0
3
Order By: Relevance
“…The T4P biogenesis machinery is composed of several sub-complexes, which are all required to form a functional system 64 (FIG. 2a).…”
Section: T4p Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The T4P biogenesis machinery is composed of several sub-complexes, which are all required to form a functional system 64 (FIG. 2a).…”
Section: T4p Biogenesismentioning
confidence: 99%
“…Figure 2b shows a hypothetical architectural model built by fitting existing structures into the densities observed by the cryo-ET studies of the M. xanthus system 84 . The ring-forming components of the T4P machinery were modeled in a 12-fold stoichiometry as this provided the best fit with cryo-ET density observed 84 , although other stoichiometries have also been proposed 64,75 . Changes that were observed in the piliated state of both systems include the pilus traversing the periplasm and extending into the extracellular space, the opening of the PilQ gate (there is an additional gate present in the longer T. thermophilus PilQ protein), and the presence of additional cytoplasmic density attributed to the elongating ATPase in both studies 83,84 (FIG.…”
Section: Structure Of T4p Machinerymentioning
confidence: 99%
“…The pilus polymer is anchored within the cell envelope by a membranespanning complex (6). Importantly, the length of the T4P is dynamic; elongation of T4P requires a cytoplasmic ATPase formed by PilB, and retraction requires its antagonist PilT (7). For Neisseria gonorrhoeae and Myxococcus xanthus, retraction of T4P generates a high mechanical force exceeding 100 pN (8,9).…”
mentioning
confidence: 99%
“…6, B and C), suggesting that the PilNO interface no longer adopts an orientation permissive for disulfide bond formation. New crystal structures of a P. aeruginosa PilM homodimer and of monomeric PilM fused to part of its binding partner, PilN (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), revealed that in the absence of PilN, the seven N-terminal residues of PilM (PilM (1-7)) bind in the PilN binding cleft of a second PilM monomer (41). Thus, PilM dimerizes in the absence of PilN.…”
Section: Piln and Pilo Homodimers May Represent A Functional Rather Tmentioning
confidence: 99%
“…Many bacteria, including Pseudomonas aeruginosa, use type IV pili (T4P) 3 for surface attachment/adhesion, biofilm formation, and twitching motility (1)(2)(3)(4)(5)(6). T4P are divided into T4aP and T4bP subgroups, based on differences in pilin size and organization of the assembly machinery (6, 7).…”
mentioning
confidence: 99%